The adventures of Beekle : the unimaginary friend - Santat, Dan. (New York : Scholastic, Inc., 2014)
An imaginary friend waits a long time to be imagined by a child and given a special name, and finally does the unimaginable--he sets out on a quest to find his perfect match in the real world.
William C. Morris Award, January 2015.
School Library Journal starred, April 2014.
New York Times, April 2014.
Horn Book, October 2014.
Bulletin (Center for Children's books), June 2014.
Kirkus Review, March 2014.
Keywords: Imaginary playmates -- Fiction; Friendship -- Fiction